Andersen–Tawil Syndrome Is Associated With Impaired PIP2 Regulation of the Potassium Channel Kir2.1 - Handklo-Jamal, Reem; Meisel, Eshcar; Yakubovich, Daniel; Vysochek, Leonid; Beinart, Roy; Glikson, Michael; McMullen, Julie R.; Dascal, Nathan; Nof, Eyal; Oz, Shimrit (Frontiers in Pharmacology, 2020)
Andersen-Tawil syndrome (ATS) type-1 is associated with loss-of-function mutations in KCNJ2 gene. KCNJ2 encodes the tetrameric inward-rectifier potassium channel Kir2.1, important to the resting phase of the cardiac action potential. Kir-channels' activity requires interaction with the agonist phosphatidylinositol-4,5-bisphosphate (PIP2). Two mutations were identified in ATS patients, V77E in the cytosolic N-terminal “slide helix” and M307V in the C-terminal cytoplasmic gate structure "G-loop". Current recordings in Kir2.1-expressing HEK cells showed that each of the two mutations caused Kir2.1 loss-of-function. Biotinylation and immunostaining showed that protein expression and trafficking of Kir2.1 to the plasma membrane were not affected by the mutations. To test the functional effect of the mutants in a heterozygote set, Kir2.1 dimers were prepared. Each dimer was composed of two Kir2.1 subunits joined with a flexible linker (i.e. WT-WT, WT dimer; WT-V77E and WT-M307V, mutant dimer). A tetrameric assembly of Kir2.1 is expected to include two dimers. The protein expression and the current density of WT dimer were equally reduced to ~25% of the WT monomer. Measurements from HEK cells and Xenopus oocytes showed that the expression of either WT-V77E or WT-M307V yielded currents of only about 20% compared to the WT dimer, supporting a dominant-negative effect of the mutants. Kir2.1 sensitivity to PIP2 was examined by activating the PIP2 specific Voltage Sensitive Phosphatase (VSP) that induced PIP2 depletion during current recordings, in HEK cells and Xenopus oocytes. PIP2 depletion induced a stronger and faster decay in Kir2.1 mutant dimers current compared to the WT dimer. BGP-15, a drug that has been demonstrated to have an anti-arrhythmic effect in mice, stabilized the Kir2.1 current amplitude following VSP-induced PIP2 depletion in cells expressing WT or mutant dimers. This study underlines the implication of mutations in cytoplasmic regions of Kir2.1. A newly developed calibrated VSP activation protocol enabled a quantitative assessment of changes in PIP2 regulation caused by the mutations. The results suggest an impaired function and a dominant-negative effect of the Kir2.1 variants that involve an impaired regulation by PIP2. This study also demonstrates that BGP-15 may be beneficial in restoring impaired Kir2.1 function and possibly in treating ATS symptoms.